Relationship between attitude towards advertisement appeals and consumer buying behaviour among young adults in Malaysia - Lee, Kar Wai; Osman, Syuhaily (Human Resource Management Academic Research Society, 2017)
The purpose of this study is to investigate the influence of young adults’ attitude towards advertisement appeals on consumer buying behaviour among young adults. Advertisement has been a very common communication tool used in marketing products to consumers. However, the attitude of young adults towards the use of these ad appeals particularly fear, sex, and guilt) and its influence on their buying behaviour is yet to be investigated in Malaysia. The empirical study was conducted at Subang Parade, Selangor and a total of two hundred respondents were selected through multistage random sampling. The results showed that young adults have likeable attitude towards both fear and guilt appeals and it showed both significant relationship towards consumer buying behaviour; whereas dislikeable attitude is shown towards sex appeal and it show non-significant relationship towards consumer buying behaviour. Multiple regressions analysis is used to examine the influence of each appeal and the most influential appeal towards consumer buying behaviour. The results found out that the most influential attitude towards consumer buying behaviour is attitude towards fear appeal. Understanding the attitude of young adults towards advertisement appeals might support the recognition of its influences and provide information towards the improvement of the use of advertisement appeals in future.